Microbiology a systems approach - Cowan, M. Kelly; Smith, Heidi (College teacher).
"This book is suited for all kinds of students and doesn't require any prerequisite knowledge of biology or chemistry. If you are interested in entering the health care profession in some way, this book will give you a strong background in the biology of microorganisms without overwhelming you with unnecessary details. Don't worry if you're not in the health professions. A grasp of this topic is important for everyone - and can be attained with this book"--Provided by publisher.
The Main Themes of Microbiology -- The Chemistry of Biology -- Tools of the Laboratory : Methods for the Culturing and Microscopic Analysis of Microorganisms -- Bacteria and Archaea -- Eukaryotic Cells and Microorganisms -- Viruses and Prions -- Microbial Nutrition and Growth -- Microbial Metabolism : The Chemical Crossroads of Life -- Microbial Genetics -- Genetic Analysis and Genetic Engineering -- Physical and Chemical Control of Microbes -- Antimicrobial Treatment -- Microbe-Human Interactions -- Host Defenses I : Overview and Nonspecific Defenses -- Host Defenses II : Specific Immunity and Immunization -- Disorders in Immunity -- Diagnosing Infections -- Infectious Diseases Affecting the Skin and Eyes -- Infectious Diseases Affecting the Nervous System -- Infectious Diseases Affecting the Cardiovascular and Lymphatic Systems -- Infectious Diseases Affecting the Respiratory System -- Infectious Diseases Affecting the Gastrointestinal Tract -- Infectious Diseases Affecting the Genitourinary System -- Microbes and the Environment -- Applied Microbiology and Food and Water Safety.
Includes index.
AU Novero (Recommending faculty) AY 2022-2023
Keywords: Microbiological Phenomena; Communicable Diseases -- microbiology; Immunity